PENGEMBANGAN REAKTOR PIROLISIS TERMAL LIMBAH PLASTIK SKALA LABORATORIUM - Prabuditya Bhisma Wisnu Wardhana; Asmar Finali; Agung Fauzi Hanafi (POLITALA PRESS, 2021)
Plastic waste damages the environment because it is not easily broken down by nature. It needs special processing of plastic waste but still does not cause environmental pollution. Thermal degradation technology is able to degrade plastic waste and turn it into useful alternative fuels. The results of this processing technology are liquid, gas and solid products. The tools used in this treatment are LPG heaters, thermal degradation furnaces and water-cooled condensers. The design capacity of this tool is 4 kg of plastic waste for one production with an operating temperature of ± 300 ° C with a processing duration of ± 120 minutes. The demand for LPG as heating is planned at ± 0.23 - 2.7 kg / hour. The materials are made of steel plates with a 3 mm thickness . The dimensions of the condenser pipe are designed to be ± 0.9 m long with a planned intake water temperature of 25 ° C.